Biologi dan Ekologi Thiaridae (Moluska: Gastropoda) di Danau Sentani Papua - Suriani Br. Surbakti (Jurusan Biologi FMIPA Universitas Cenderawasih, 2011)
Lake Sentani has been subjected to multi-pronged pressures, involving both internal and external factor. Yet, ecologists researching the lake generally, conduct studies on water quality, but less attention was paid towards faunal diversity and biological resources potentials of the lake. This research is focused on the diversity of Thiaridae species (Gastropoda). The research was conducted for two months from October to November 2009 using line transect methods in settlement and no settlement areas, inlet and outlet areas. The transects was installed in the lake from the shoreline at 0 to 0.5m depth and 0.5 to 1.0m depth and 1.0 to 1.5 m depth. At each depth sample, 4 points were taken. Transect at each location, repetition was repeated 4 times. The results brought in the diversity of Thiaridae as 7 species, namely Tiara scabra and Melanoides granifera, Melanoides tuberculata, Melanoides canalis, Melanoides copali, Melanoides sentaniensi, Stelomelania sp. The highest diversity were found in no settlement region with a value of H was 0.65 and the lowest were found in residential area with a H value was 0.57, inlet area was 0.59 and outlet area was 0.34. Density in no settlement areas was 0.36, inlet area was 1.84 and outlet area was 0.64. Environmental parameters was also assessed in this study, such as temperature, pH, DO, phosphorus, nitrite and nitrate. Key words: threat, Lake Sentani, diversity, density, Mollusc.